2018
DOI: 10.1016/j.phro.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center output factor intercomparison to uncover systematic inaccuracies in small field dosimetry

Abstract: A B S T R A C TLarge uncertainties in output factor (OF) small fields dosimetry motivated multicentric studies. The focus of the study was the determination of the OFs, for different linacs and radiosurgery units, using new-generation detectors. Intercomparison studies between radiotherapy centers improved quality dosimetry practices. Results confirmed the effectiveness of the studies to uncover large systematic inaccuracies in small field dosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Twenty‐four papers/reviews/letters have been published on top 50% ranking Radiation Oncology journals in 2014–2019 period, 18–40 with authors list selected according to Vancouver recommendations. In detail, 15 full papers 19–23,28–32,34–36,38,40 . 5 reviews, 18,27,33,37,41 1 editorial, 25 and 3 letters to the editor 24,26,39 were published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐four papers/reviews/letters have been published on top 50% ranking Radiation Oncology journals in 2014–2019 period, 18–40 with authors list selected according to Vancouver recommendations. In detail, 15 full papers 19–23,28–32,34–36,38,40 . 5 reviews, 18,27,33,37,41 1 editorial, 25 and 3 letters to the editor 24,26,39 were published.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, 15 full papers. [19][20][21][22][23][28][29][30][31][32][34][35][36]38,40 5 reviews, 18,27,33,37,41 1 editorial, 25 and 3 letters to the editor 24,26,39 were published. A total of more than 100 medical physicists were authors of at least one article, showing high level of members' engagement.…”
Section: B Engagement Metricsmentioning
confidence: 99%
“…This has been recently addressed by the publication of the IAEA code of practice [41] but the accurate modelling of small fields and how the correct detector is used to collect the commissioning data is still challenging. Several groups [11,12,21] conducted national and multi-national audits respectively, of calculated small field output factors by comparing with standardised data published by the IROC-Houston QA center at MD Anderson [22,23,42] and found that not all centres were modelling these fields well. The audits found that the deviations increased with decreasing field size and the treatment planning system commonly overestimated in comparison with the reference data.…”
Section: Advanced Techniquesmentioning
confidence: 99%
“…Dosimetry audit is a key component in quality management programmes in radiotherapy, playing an important role in the safe implementation of new treatment modalities and techniques [1][2][3][4]. National and large scale audits provide data which can help to create, sustain and increase standards as well as have the potential to identify issues which may cause harm to patients, thus improving both quality and safety [1,[4][5][6][7][8][9][10][11][12][13]. They can also help to reduce variability in dose delivered to the patient both nationally, internationally and within multi-institutional trials [3,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%